FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN IMPOR BERAS DI TIMOR-LESTE (2004-2011) - , Benigno Da Costa Guterres; , Atidiatun Adji, M.Ec., M.A., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to analyze the factors that influence the demand for rice imports in Timor-Leste (2004-2011). The data used in this study is secondary data in the form of time series data (time series) per quarter for the past 8 years. The analytical tool used in this research is descriptive analysis and multiple linear regression analysis using EViews6 software. The results descriptively shows the average demand for rice imports by 11504.849 kg with the lowest demand are 4699.186 kg and the highest demand are 27570.615 kg. Average local rice production amounted 12086.45 kg with local rice production the lowest are 5398.83 kg and the highest are 20396.17. The results of the regression analysis showed that the production of local rice, local rice prices and the demand for imported rice prior periods have a positive and significant impact on import demand for rice in Timor-Leste in 2004-2011. Per capita income, population and exchange negatively and significant effect on demand for rice imports in Timor-Leste in 2004-2011, while import prices negatively affect the demand for rice imports in Timor-Leste in 2004-2011.